KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN DENGAN KETERAMPILAN MENULIS TEKS PIDATO PERSUASIF SISWA KELAS IX SMP NEGERI 13 MUKOMUKO - Inti Ikhalasani; Syahrul R. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to describe the following matters. First, to describe the environmental vocabulary mastery of grade IX students at SMP Negeri 13 Mukomuko. Second, to describe the level of persuasive speech text writing skills of grade IX students at SMP Negeri 13 Mukomuko. Third, to describe the correlation of vocabulary mastery in the environmental field with the persuasive speech text writing skills of grade IX students of SMP Negeri 13 Mukomuko. This type of research is a quantitative study with a correlational method. The research design used was a two-variable correlational relationship. There are three research results. First, the environmental vocabulary mastery of class IX students of SMP Negeri 13 Mukomuko are in good qualifications with an average counting of 76,13. Second, the skills of writing persuasive speech text of the IX grade students of SMP Negeri 13 Mukomuko are more than adequate with an average count of 70,37. Third, there is a significant correlation between vocabulary mastery in the environmental field with the persuasive speech text writing skills of grade IX students of SMP Negeri 13 Mukomuko with n-1 degrees of freedom and a significant level of 95%. H0 is rejected and H1 is accepted because tcount (4,94) is greater than ttable (1,68).  Kata kunci: korelasi, penguasaan kosakata bidang lingkungan, keterampilan menulis teks pidato persuasif